2016
DOI: 10.1016/j.neuropsychologia.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Eccentricity effects in vision and attention

Abstract: Stimulus eccentricity affects visual processing in multiple ways. Performance on a visual task is often better when target stimuli are presented near or at the fovea compared to the retinal periphery. For instance, reaction times and error rates are often reported to increase with increasing eccentricity. Such findings have been interpreted as purely visual, reflecting neurophysiological differences in central and peripheral vision, as well as attentional, reflecting a central bias in the allocation of attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 47 publications
(78 reference statements)
7
51
1
Order By: Relevance
“…Our investigations into face-related processing in central to parafoveal locations (up to 4) revealed that, as expected, faces, as well as all tested categories, show an eccentricity effect (i.e. reduced accuracy and d-prime and slower RTs with growing eccentricity 6 . While we anticipated finding that face related processing may outperform other categories at the central visual field (see model in Fig.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our investigations into face-related processing in central to parafoveal locations (up to 4) revealed that, as expected, faces, as well as all tested categories, show an eccentricity effect (i.e. reduced accuracy and d-prime and slower RTs with growing eccentricity 6 . While we anticipated finding that face related processing may outperform other categories at the central visual field (see model in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…One of the main coding principles in the visual cortex is eccentricity, where the foveal representation is significantly magnified in the visual cortex relative to its size on the retina, and as distance from the fovea grows, the cortical representation is reduced [1][2][3] . This foveal magnification is assumed to be the main factor contributing to reduced performance with growing eccentricity for multiple (but not all) visual tasks [4][5][6] . It has also been shown that this foveal enhancement can be overcome if peripheral information is scaled to match the cortical representation (aka M-scaling 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staugaard et al (2016) reported further that manipulating endogenous attention did not alter these attentional gradients, but cited Proksch and Bavelier’s (2002) study to support the claim that long-term environmental factors may lead to a compensatory trade-off between attentional resources in peripheral vs. central vision.…”
Section: Introductionmentioning
confidence: 94%
“…First, walking requires visual control of the upcoming area to avoid falls or collisions (Imai et al, 2001;Nomura et al, 2005); as a consequence, an additional visual task will rely on the same resources which are necessary to visually control walking and thus compete (Wickens et al, 1983;Wickens, 2002). Secondly, the sensory features and position of additional visual stimuli (eccentricity in the visual field) have a strong impact on visual information processing (Carrasco et al, 1995;Staugaard et al, 2016). Therefore, detecting peripheral and potentially less salient visual stimuli might require more attentional resources compared to more centrally ones, revealing a higher dual-task cost when concurrently walking.…”
Section: The Importance Of Ecological Validitymentioning
confidence: 99%